Location Advantage but Limited Leisure Demand: Sentiment Analysis of Guest Reviews at Permata Hotel Bogor near Kebun Raya Bogor - Muhamad Andriana; Kadek Wiweka; Ramon Hurdawaty (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze guest perceptions of Permata Hotel Bogor through sentiment analysis of Google Reviews and to examine the gap between location advantage and the resulting tourism experience. The research employs a lexicon-based sentiment analysis approach using AFINN (scoring) and Bing (sentiment classification) methods on approximately 4,661 Indonesian-language reviews. The findings reveal that sentiment distribution is dominated by neutral reviews (±80 - 83%), followed by positive (±13 - 15%) and negative sentiments (±2 - 5%). Concentration of sentiment scores around zero indicates that guest experiences are largely descriptive and lack strong emotional engagement. Despite this, the hotel maintains a relatively high average rating (±4.0, ranging from 3.8 to 4.2), suggesting a gap between cognitive evaluation and affective experience. Textual analysis shows that the hotel’s main strengths lie in its strategic location near the Bogor Botanical Gardens, comfortable rooms, and basic facilities, while its main weaknesses are related to service quality, cleanliness, and maintenance, reflecting service inconsistency. Segment analysis indicates that the FAMILY segment tends to be more positive, the BUSINESS segment is dominated by neutral sentiment, and SOLO travelers are the most critical. Temporal analysis shows relatively stable performance with slight improvement in the post-pandemic period, yet without a significant increase in positive sentiment. Findings indicate the presence of Tourism Spillover Failure, where location advantage fails to translate into leisure demand due to the dominance of functional experience. This research highlights the importance of transforming service delivery into experience-driven hospitality to enhance emotional engagement and improve hotel competitiveness.